2013
DOI: 10.1111/gcbb.12085
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle greenhouse gas emissions of furniture and bioenergy production from oil palm trunks

Abstract: The palm oil industry constantly attempts to increase the sustainability along the entire palm oil value chain. One important strategy is to utilize all co-products. Oil palm trunks, which become available upon replanting of existing plantations, represent an important and increasing flow of underexploited biomass. In recent years, innovative technologies are emerging to use them for producing furniture or plywood or providing bioenergy. We assessed the life cycle greenhouse gas emissions of such products and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…Under the test conditions, it was observed that the impact properties of loss energy and damping index decreased with increasing fiber content. The impact behavior of composites of green composite oil palm frond is nevertheless, noted to be with observed in both natural and synthetic fibres as reinforcements in composite production, as reported by Sreekala et al [5]. …”
Section: Izod Impact Strength Propertiessupporting
confidence: 53%
See 1 more Smart Citation
“…Under the test conditions, it was observed that the impact properties of loss energy and damping index decreased with increasing fiber content. The impact behavior of composites of green composite oil palm frond is nevertheless, noted to be with observed in both natural and synthetic fibres as reinforcements in composite production, as reported by Sreekala et al [5]. …”
Section: Izod Impact Strength Propertiessupporting
confidence: 53%
“…When compared with other natural plants, oil palm frond fibres are tough, and generally exhibit moderate degrees of elasticity and plasticity [4], additionally, oil palm stem and frond fibres are noted to contain large amount of lignin, with very porous and lacuna-like cross-section with varying diameters, which affect their mechanical properties, such as high ductility, but with lower tensile strength than most other natural plant fibres. Recent studies indicate that oil palm industries continually attempt to increase the sustainability of palm oil value chain by utilizing all co-products, including the issues of life cycle greenhouse emissions of furniture and bioenergy production from oil palm trunks [5]. The utilization of oil palm frond fibre in composite production for other applications will no doubt compliment the value chain realization goal.…”
Section: Introductionmentioning
confidence: 99%
“…The preceding discussion suggests traditional resin as a hot spot for formaldehyde emissions. This synthetic resin greatly influences primary environmental impact categories for two reasons: First, the composition of PF is basically of fossil origin, especially phenol obtained from fossil resources due to environmental factors related to the use of fossil fuels; and second, free formaldehyde is released into the air during the subsystems of veneer compositing, gluing, and hot pressing [19,20,21]. Therefore, we propose solutions to improve the environmental performance of plywood based on reducing consumption of PF resin and replacing petroleum-based phenol with bio-oil produced by biomass fast pyrolysis; such pyrolysis contains many phenolic compounds, such as phenol, guaiacol, and 4-methyl guaiacol that can be condensed with formaldehyde [22].…”
Section: Discussionmentioning
confidence: 99%
“…(Yuan et al 2019) Such approaches not only can reduce carbon emissions, but also they follow the guidelines of sustainable design. For example, oil palm trunks with no commercial value in the palm oil industry chain usually decays into waste, but using them to make furniture can effectively reduce greenhouse gas emissions, although the energy consumption of wood processing is higher due to material properties (Rettenmaier et al 2014) Compared with wood materials, the auxiliary materials of solid wood furniture are all high-emission materials. Therefore, reducing the use of chemical agents and metal connectors is the primary goal.…”
Section: Carbon Reduction Materials Selectionmentioning
confidence: 99%